Dual Activation of Phosphodiesterases 3 and 4 Regulates Basal Spontaneous Beating Rate of Cardiac Pacemaker Cells: Role of Compartmentalization? - Vinogradova, Tatiana M.; Kobrinsky, Evgeny; Lakatta, Edward G. (Frontiers in Physiology, 2018)
Spontaneous firing of sinoatrial (SA) node cells (SANCs) is regulated by cyclic adenosine monophosphate (cAMP)-mediated, protein kinase A (PKA)-dependent (cAMP/PKA) local subsarcolemmal Ca2+ releases (LCRs) from ryanodine receptors (RyR). The LCRs occur during diastolic depolarization (DD) and activate an inward Na+/Ca2+ exchange current that accelerates the DD rate prompting the next action potential (AP). Basal phosphodiesterases (PDEs) activation degrades cAMP, reduces basal cAMP/PKA-dependent phosphorylation, and suppresses normal spontaneous firing of SANCs. The cAMP-degrading PDE1, PDE3, and PDE4 represent major PDE activities in rabbit SANC, and PDE inhibition by 3-isobutyl-1-methylxanthine (IBMX) increases spontaneous firing of SANC by ∼50%. Though inhibition of single PDE1–PDE4 only moderately increases spontaneous SANC firing, dual PDE3 + PDE4 inhibition produces a synergistic effect hastening the spontaneous SANC beating rate by ∼50%. Here, we describe the expression and distribution of different PDE subtypes within rabbit SANCs, several specific targets (L-type Ca2+ channels and phospholamban) regulated by basal concurrent PDE3 + PDE4 activation, and critical importance of RyR Ca2+ releases for PDE-dependent regulation of spontaneous SANC firing. Colocalization of PDE3 and PDE4 beneath sarcolemma or in striated patterns inside SANCs strongly suggests that PDE-dependent regulation of cAMP/PKA signaling might be executed at the local level; this idea, however, requires further verification.